(untitled) (International Journal of Ayurveda and Pharma Research, 2016)
Obesity is a complex interplay between environmental and genetic factors, is also associated with significant morbidity and mortality. The primary objective of the present study was to evaluate the efficacy and safety of Calebin A (standardized extract of Curcuma caesia) in the management of weight in obese or overweight individuals. A randomized, mono-centric, double-blind, placebo-controlled, clinical study was conducted by administering Calebin A (standardized extract of Curcuma caesia) capsules (25 mg, one capsule twice a day) and indistinguishable placebo capsules as daily supplements to 40 overweight and obese subjects for 90 days. The study participants were divided in 1:1 ratio to receive either Calebin A (standardized extract of Curcuma caesia) (n = 20) or placebo (n = 20). Efficacy was assessed by measuring body weight, body mass index, leptin, adiponectin levels, total cholesterol, HDL cholesterol, LDL cholesterol, triglycerides and Hs-CRP. Safety was assessed by evaluating safety parameters (vital signs and laboratory investigations) and monitoring adverse events. After 90 days, significant reduction in body weight (P< 0.0001) and body mass index (P < 0.0001) were observed in the Calebin A (standardized extract of Curcuma caesia) group compared with placebo. Additionally, significant change in serum biomarkers was observed between Calebin A (standardized extract of Curcuma caesia) and placebo groups from baseline to final visits. Adverse events were mild and were unrelated to the investigational products. Supplementation with Calebin A (standardized extract of Curcuma caesia) resulted in significant decrease in weight loss than placebo over 90 days. It was safe and well tolerated by all subjects.